Food Insecurity and Malnutrition in Rural Tanzania: Mapping Perceptions for Social Learning. Issue 6 (2nd November 2021) - Bonatti, Michelle; Borba, Juliano; Bundala, Nyamizi; Löhr, Katharina; Ito, Larissa Hery; Rybak, Constance; Sieber, Stefan
ABSTRACT: In Tanzania, a high level of hunger persists. Several factors compound a complex scenario of food insecurity. Contextual aspects at the community level can influence the maintenance of the vulnerable local conditions. This article aims to better understand these aspects by investigating community problem perceptions in n = 04 remote rural villages in Tanzania. Furthermore, how to include community perceptions as a pedagogical element of food security projects is discussed. The methodology consists of three steps: preparatory exploration; household survey (n = 663); and pedagogical workshops (n = 270). The main results indicate that inhabitants of the four villages identify and describe their problems differently. We discovered food insecurity's hidden factors. Community problem perceptions and local knowledge play fundamental roles in critical food security, despite the environmental conditions' effect (lack of infrastructure, water scarcity). The pedagogical process of Codification and Decoding of hunger situations can generate more effective educational programs for social learning.